How Does Self-Sacrificial Leadership Foster Knowledge Sharing Behavior in Employees? Moral Ownership, Felt Obligation and Supervisor-Subordinate Guanxi - Su, Xiaofeng; Jiang, Xiaoli; Xie, Guihua; Huang, Meijiao; Xu, Anxin (Frontiers in Psychology, 2022)
Recent trends in the academic literature indicate growing interest in leadership for fostering employees’ knowledge sharing. In this research, we integrate social cognitive theory and social exchange theory to explain how and when self-sacrificial leaders promote employee knowledge sharing. It is found that self-sacrificial leaders influences employees’ knowledge sharing by nurturing employee moral ownership and a sense of obligation to the organization. We also found the moderating effect of supervisor-subordinate guanxi on the self-sacrificial leadership - employees’ knowledge sharing link.We discuss the implications of these findings for understanding and promoting self-sacrificial leaders and employees’ knowledge sharing behaviors in the workplace.